IMPLEMENTASI MEDIA GAMBAR TERHADAP MENULIS CERITA PENDEK DI KELAS XI SMA NEGERI 1 KUNINGAN - Azkiya, Rana Nur; Ropiah, Opah (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2024)
The purpose of this research is to determine student’s ability to write short stories using pictures media. The method used in this research is an experiment with a quantitative approach and a one-group pretest-posttest design. The instruments used are pretest and posttest. The data analysis techniques employed are validity tests, normality tests, and paired sample t-tests. This research was conducted at SMA Negeri 1 Kuningan with a sample of 30 students from class XI-3. The result of this research are: 1) students’ ability to write short stories before using picture media was still far from the Minimum Mastery Criteria (MMC) with an average score of 72,16; 2)students’ ability to write short stories after using picture media improved with an average score of 85,83; 3) based on the t-test (paired sample t-test ), the alternative hypothesis (Ha) is accepted, and the null hypothesis (H0) is rejected because the significance value (2-tailed) is 0.000 < 0.05. Therefore, it can be concluded that the implementation of picture media has a significant effect on students’ writing ability in short story lessons in class XI at SMA Negeri 1 Kuningan. Thus, it is also recommended for teachers to apply this method in their teaching.